1994
DOI: 10.1113/expphysiol.1994.sp003806
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of aldosterone and oxytocin to influence renal sodium excretion in rats

Abstract: SUMMARYThe possibility of an interaction between oxytocin and aldosterone to influence renal Na+ excretion was investigated in Inactin-anaesthetized male Sprague-Dawley rats. Endogenous plasma concentrations of aldosterone were suppressed by either adrenalectomy or bicarbonate infusion. The effects of 2 h intravenous administration of oxytocin (0-04 pmol/min) and/or aldosterone (42 pmol/min) on renal Na+ handling were studied in 0077 M NaCl-infused adrenalectomized (Adx) rats and groups of intact animals that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
1
4
0
1
Order By: Relevance
“…Oxytocin can exert a natriuretic action in the rat (10); it is required to restore renal sodium excretion after neurohypophysectomy (3) and in adrenalectomized or aldosterone-suppressed rats (28). Hence, the natriuresis observed after longterm rhRLX infusion could have been mediated, at least in part, by oxytocin.…”
Section: Discussionmentioning
confidence: 99%
“…Oxytocin can exert a natriuretic action in the rat (10); it is required to restore renal sodium excretion after neurohypophysectomy (3) and in adrenalectomized or aldosterone-suppressed rats (28). Hence, the natriuresis observed after longterm rhRLX infusion could have been mediated, at least in part, by oxytocin.…”
Section: Discussionmentioning
confidence: 99%
“…Ganong and Mulrow (9) observed a reduction in urinary sodium excretion in adrenalectomized dogs 5-30 min after a bolus injection of aldosterone into the aorta or renal artery. In contrast, our laboratory has previously reported that combined infusion of aldosterone and oxytocin into aldosterone-suppressed rats (adrenalectomy or sodium bicarbonate infusion) resulted in a rapid increase in urinary sodium excretion (26), contrary to the conventional, genomic antinatriuretic actions of aldosterone. Apart from these observations, little is known about the nongenomic actions of aldosterone in the intact animal.…”
mentioning
confidence: 76%
“…Rats either continued to receive vehicle (2.5% dextrose, n ϭ 8) for the remaining 3 h of the experiment or received vehicle for 1 h, followed by aldosterone (42 pmol/min, Sigma-Aldrich, Poole, Dorset, UK) for 1 h and then vehicle for the final hour (n ϭ 9). Our laboratory has shown previously that this dose alters renal function in aldosterone-suppressed rats while inducing circulating concentrations within the physiological range (26). Urine samples were collected for the measurement of electrolytes and 3 H inulin.…”
Section: Experimental Protocolmentioning
confidence: 99%
“…One of the earliest reports of rapid actions of aldosterone on sodium transport in the kidney was in 1957 when Cole described the rapid effect of aldosterone administration for 30 min to cause a reduction in urinary loss of Na + and increased reabsorption by the renal tubules in response to intravenously administered saline in adult male rats [18]. It has also been documented that aldosterone infusion into aldosterone-suppressed rats (by adrenalectomy or infusion with sodium bicarbonate) resulted in the rapid increase in urinary Na + excretion [19]. The rapid non-genomic actions of aldosterone in vivo were further demonstrated in the intact rat when aldosterone induced a rapid increase in urinary Na + excretion within 15 min [20].…”
Section: Non-genomic Actions Of Aldosterone On Ion Transportersmentioning
confidence: 99%